The Role of Quality in Improving Health Systems: A Review - Almiftah, Mohammad Ali; Bakhsh, Eshraq Talal; Alsulami, Rahmah Muith; Alzahir, Ghadeer Ali; Alobairi, Hatem Mohammed; Alhejji, Amani Ali; Alsaadi, Nouf Abdulrahman; Alzahir, Lujain Ali; Alshakhouri, Zainab Ameen; Alaradi, Eman Abdulaziz; et al. (Journal of Posthumanism, 2024)
The fundamental imperative of modern healthcare systems is the persistent delivery of high-quality services, which is intrinsically linked to improved patient outcomes and systemic efficiency. Sustained global challenges, however, necessitate a critical examination of quality’s multifaceted role in health system improvement, particularly amidst technological advancements and evolving patient expectations. This review was conducted to synthesize current academic discourse on the role of quality in enhancing health systems, focusing specifically on conceptualizations of quality, the impact of various quality improvement initiatives, and the emerging challenges and opportunities, such as those presented by Artificial Intelligence (AI). Major findings indicate that quality is conceptually diverse, encompassing patient-centered measures like subjective well-being and therapy adherence, alongside organizational factors such as High Reliability Organization (HRO) principles and organizational culture. Furthermore, accreditation, Continuous Quality Improvement (CQI) programs, and the adoption of AI-driven tools demonstrate significant, yet variable, positive effects on service quality and patient satisfaction. Critically, challenges persist in managing resource constraints and addressing the potential negative impact of privatization on care quality. Recommendations underscore the need for integrated, patient-centric quality metrics, robust leadership for quality initiatives, and strategic investment in AI and distributed systems to overcome existing barriers. In conclusion, the evidence strongly supports a holistic, continuously managed approach to quality as the bedrock for effective health system reform, necessitating a paradigm shift towards proactive, data-informed, and culturally embedded quality assurance for sustainable improvement and enhanced global health security.